Primary midgut volvulus without intestinal malrotation in a young adult: a case report. Issue 6 (1st November 2020) - De Hous, Nicolas; de Gheldere, Charles; Salgado, Rodrigo; Gryspeerdt, Filip
Abstract: Background: Midgut volvulus is a rare cause of acute abdomen characterized by a twisting of the entire small intestine around its mesenteric pedicle. It is a well-known complication of intestinal malrotation usually occurring in infants and young children. We report a rare case of a midgut volvulus without any underlying condition occurring in a young adult. Case presentation: A 24-year-old male was admitted to our surgical department with symptoms and signs of small bowel obstruction. The abdominal computed tomography (CT) scan showed dilatation of the entire small intestine and a rotation of the mesentery. The patient underwent an urgent explorative laparoscopy with conversion to median laparotomy, revealing a midgut volvulus with marked intestinal ischemia. Mesenteric fixation was normal but the mesenteric pedicle was described as relatively narrow. The midgut volvulus was untwisted with subsequent recovery of the intestinal ischemia. Results: The postoperative period was marked by prolonged ileus requiring nasogastric tube decompression that gradually resolved after 1 week. The patient was discharged on the tenth postoperative day. He had fully resumed his daily activities 1 month after surgery and had experienced no recurrent symptoms 6 months later. Conclusion: Primary midgut volvulus is an extremely rare condition that must be considered in all young adults presenting with intestinal obstruction without previous abdominal surgery. Early diagnosis and immediate surgical intervention are the key factors to a successful outcome.